PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PENIPUAN TENAGA KERJA KE LUAR NEGERI YANG DILAKUKAN OLEH OKNUM DI KABUPATEN BULELENG - Komang Mirah Anggunning (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
The purpose of this study was to determine (1) the Implementation of Legal Protection for Victims of Criminal Acts of Migrant Worker Fraud Abroad by Placing Agents in Buleleng Regency and (2) the Role of Related Agencies in Buleleng Regency in Assisting in Prosecuting Migrant Worker Fraud Cases. The research method used is empirical law. Data were obtained through document studies, observations, and interviews with related parties. The results of the study are (1) Although several steps have been taken to protect victims of migrant worker fraud in Buleleng Regency, these steps have not yet been implemented optimally. This is caused by the continued occurrence of unofficial departures, the lack of public knowledge about legal procedures, and the absence of supervision of the actions of unofficial placement agents. (2) The role of related agencies in taking action, namely; the Buleleng Manpower and Transmigration Office plays a role in data collection, mediation, and verification of official agents through the Siap Kerja application; the Singaraja Immigration Office supervises documents and issuance of passports; The Buleleng Police handle law enforcement based on Article 378 of the Criminal Code and Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, despite being hampered by cross-border jurisdiction.